Root canal configuration of human permanent anterior teeth: a cross-sectional study using cone-beam computed tomography in the Pakistani population - Nasim, Hina; Shakeel Kazmi (Journal of the Pakistan Medical Association, 2024)
Objective: To analyse and document internal root morphological variations in permanent anterior teeth using cone-beam computed tomography. Methods: The cross-sectional, retrospective study was conducted from January 21 to June 19, 2021, at Jinnah Magnetic Resonance Imaging and Body Scan, and comprised data from July to December 2020 related to all the patients who had been referred to the centre for dental cone-beam computed tomography scan. The scans were evaluated at the Radiology Department of the School of Dentistry at Shaheed Zulfiqar Ali Bhutto Medical University, Islamabad, Pakistan. The morphology of the roots and root canals in all permanent anterior teeth was examined. Root canal configuration was categorised using Vertucci’s classification. Data was analysed using SPSS 20. Results: Of the 211 patients, 116(55%) were females and 95(45%) were males. The overall mean age was 39.9±1.02 years (range: 15-65 years). All the permanent anterior teeth exhibited a single root, with the exception 2(0.9%) mandibular right and 4(1.9%) left canines which had double roots. Type I root canals were observed in all 211 (100%) maxillary right central incisors, maxillary left central incisors and maxillary left canines. Among maxillary right canines, 208(98.6%) had type-I root canals, and the corresponding value for maxillary right lateral incisors was 209(99.1%), and for maxillary left lateral incisors, the value was 210(99.5%). Root canal polymorphism had no significant association with gender (p>0.05). Conclusion: The presence of type-I root canal was common in permanent anterior teeth, and there was significant association of root canal polymorphism with gender. Key Words: Cone-beam computed tomography, Dental pulp cavity, Anterior teeth, Vertucci’s classification.